2017
DOI: 10.1080/00397911.2017.1385084
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of some novel triazolo[3,4-b]thiadiazines and triazolo[4,3-b]tetrazines

Abstract: EXPERIMENTALMelting points were measured on an Electrothermal IA 9000 series digital melting point apparatus. IR spectra were recorded in potassium bromide discs on Pye Unicam SP 3300 and Shimadzu FTIR 8101 PC infrared spectrophotometers. NMR spectra were recorded on a Varian Mercury VX-300 NMR spectrometer operating at 300 MHz ( 1 H NMR) or 75 MHz ( 13 C NMR) and run in deuterated dimethylsulfoxide (DMSO-d6). Chemical shifts were related to that of the solvent. Mass spectra were recorded on a Shimadzu GC-MS-Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The reaction of 4-amino-5-substituted-4H-1,2,4-triazole-3-thiols 1 with hydrazonoyl chlorides 2 in refluxing ethanol or dioxane with Et 3 N afforded (7Z)-7- [2-(aryl)hydrazinyli dene]-6-methyl-7H- [1,2,4]triazolo [3,4-b] [1,3,4]thiadiazines 3 [6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The produced compounds underwent in vitro testing against 11 candida species and were compared to the conventional medication ketoconazole.…”
Section: Synthesis Of Triazolo[34-b]thiadiazinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of 4-amino-5-substituted-4H-1,2,4-triazole-3-thiols 1 with hydrazonoyl chlorides 2 in refluxing ethanol or dioxane with Et 3 N afforded (7Z)-7- [2-(aryl)hydrazinyli dene]-6-methyl-7H- [1,2,4]triazolo [3,4-b] [1,3,4]thiadiazines 3 [6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The produced compounds underwent in vitro testing against 11 candida species and were compared to the conventional medication ketoconazole.…”
Section: Synthesis Of Triazolo[34-b]thiadiazinesmentioning
confidence: 99%
“…Scheme 1. Synthesis of - [1,2,4]triazolo [3,4-b] [1,3,4]thiadiazines 3A [6], 3B [9], and 3C [23]. 4-Amino-5-substituted-4H-1,2,4-triazole-3-thiols 1 were treated with ethyl 3-bromo-2-oxopropanoate 4 in ethanol at reflux to afford ethyl triazolothiadiazine-6-carboxylate 5A,B.…”
Section: Synthesis Of Triazolo[34-b]thiadiazinesmentioning
confidence: 99%
“…Products of the reactions between 4-amino-3-mercaptotriazoles and hydrazonoyl halides are [1,2,4]triazolo[3,4- b ][1,3,4]thiadiazines bearing 2-arylhydrazono group at the 7-position. Abdelrazek et al [ 44 ] reported the facile triethylamine-catalyzed synthesis of 3-ethyl-6-methyl-7-(2-arylhydrazono)-7 H -[1,2,4]triazolo[3,4- b ][1,3,4]thiadiazine derivatives ( 59 ) from the reaction of 4-amino-5-ethyl-3-mercapto-1,2,4-triazole ( 1 ) with variously substituted hydrazonoyl chlorides ( 57 ) in refluxing dioxane. S -alkylated intermediates ( 58 ), generated in situ, are cyclized to afford the desired products ( 59 ) in good yields (80–88%) (Scheme 25 ).…”
Section: Synthetic Approaches To the 124-triazolo[34- B ][134]thiadiazine Scaffoldmentioning
confidence: 99%
“…In these last two decades, we have launched a program designed to create new easy, synthetic paths to heterocyclic systems that are functionally replaced, using inexpensive laboratory materials with anticipated bioactivities . Under our program, some new pyridine‐fused aza heterocyclic compounds have to be evaluated for biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] In these last two decades, we have launched a program designed to create new easy, synthetic paths to heterocyclic systems that are functionally replaced, using inexpensive laboratory materials with anticipated bioactivities. [32][33][34][35][36][37][38][39][40][41][42] Under our program, some new pyridine-fused aza heterocyclic compounds have to be evaluated for biological activity. It was expected that combining a triazole ring with a pyridine and/or a pyrimidine ring in one system could lead to improved biological activity.…”
Section: Introductionmentioning
confidence: 99%